On‐line monitoring of a BNR process using in situ ammonium and nitrate probes and biomass nitrification‐denitrification rates in an intermittently aerated and pulse fed bioreactor. Issue 10 (28th October 2013) - Melidis, Paraschos; Ntougias, Spyridon; Sertis, Christos
Abstract BACKGROUND The need to monitor and optimize biological nitrogen removal (BNR) processes has led to the use of on‐line instrumentation. In situ located sensors can monitor in a real‐time mode the dynamics of microbial processes, providing the opportunity to understand and optimize process performance. RESULTS A nitrification–denitrification process was monitored on‐line for the first time in an intermittently aerated and pulse fed activated sludge system using in situ located sensors for ammonia and nitrate. Pulse feeding created a reduced C/N ratio gradient across the anoxic phase, resulting in complete denitrification within a period of 20 min. Two denitrification rates were determined, corresponding to nitrate reduction during utilization of the readily biodegradable (0.110–0.246 g g‐1 d‐1) and the slowly (particulate) biodegradable (0.032–0.041 g g‐1 d‐1) COD, respectively. Despite the fact that the initial C/N ratio at both Food/Microorganism ratio (F/M) 0.20 and 0.28 was decreased from 4.8 to 1.8 at the end of the anoxic phase, the C/N ratio decrease was twice as fast at the higher F/M ratio. CONCLUSION Pulse‐feeding resulted in higher C/N ratios at the beginning of the anoxic phase, creating a reduced C/N ratio gradient during the denitrification period. Organic load was mostly consumed during the anoxic phase, resulting in high nitrification efficiency, low oxygen requirement and saving energy. © 2013 Society of Chemical Industry